The effects of three weight management methods on body composition and serum lipids of overweight and obese people - Cai, Jingjing; Shao, Lin; Zhao, Shilong; Liu, Wen; Liu, Peng (Frontiers in Nutrition, 2022)
Introduction： To explore the improvement effect of a Calorie-restricted diet (CRD), 5+2 Intermittent fasting (5+2IF), and high protein diet (HPD) on weight composition and serum lipid level of overweight and obese people in a short period (3 months). Methods： Fifty-three participants aged 18-60 years old and with BMI ranging from 24 kg/m² to 35 kg/m² were screened for inclusion and exclusion criteria and were randomly divided into CRD, 5+2 IF, and HPD three groups. Basic information, body composition, and venous blood samples were collected at baseline and after 3 months of intervention. Body Composition was measured by a body composition analyzer (SK-V9) and serum lipids were assayed using the Roche Cobas e702 automatic biochemistry analysis system. The generalized estimating equation (GEE) was used to analyze and compare the repeated measurements of body composition and levels of serum lipids. Results： The results showed that total weight, BMI, body fat mass, muscle mass, visceral fat index, waist and hip circumferences had significantly decreased in all three groups after 3-months intervention and the average weight loss was 3.3±1.14 kg, 4.12±0.05 kg and 2.62±0.13 kg in CRD, 5+2 IF and HPD three groups, respectively. The results of the GEE model indicated that, compared with the CRD group, the 5+2 IF group showed a more significant decrease in weight (β=-0.272, P<0.001), BMI (β=-0.091, P<0.001), body fat mass (β=-0.172, P<0.001), muscle (β=-0.043, P<0.001) and visceral fat index (β=-0.019, P<0.001), however, HPD has more advantages in visceral fat index loss (β=-0.011, P<0.001) and lean body mass preserve (β=0.229, P<0.001). Conclusion： Our findings showed that the 5+2 IF may be more effective in reducing total weight and body fat, and a high protein diet may be more helpful in preventing lean body mass loss during a short-term weight loss intervention.